Articulatory modelling of coronal stop contrasts in Wubuy - Proctor, M.; Bundgaard-Nielsen, R.; Best, C.; Goldstein, L.; Kroos, Christian; Harvey, M. (Australasian Speech Science and Technology Association (ASSTA), 2010)
Like many Australian languages, Wubuy (aka Nunggubuyu) uses four contrastive coronal stops. The phonological basis of this contrast is not well understood, as it is not known to what extent phonological primitives are grounded in the phonetic domain. We introduce a preliminary gestural computational model of Wubuy phonology being developed as an extension of the Task Dynamics Application (TaDA: [1, 2]). Coronal stops are modeled as recurrent dynamic structures of coordinative tongue tip and tongue body gestures, contrasting in constriction degree and location. Articulatory kinematics produced by gestural models are qualitatively compared with EMA data obtained from a Wubuy speaker producing the same segments. The implications of these experiments for theories of phonological representation are discussed.